Agriculture in the atlantic zone of Costa Rica: summarizing report of an exploratory survey - Slyus, F.R. van; Wielemaker, W.G.; Wienk, J.F. (CATIE, Turrialba (Costa Rica). Agricultural Univ. of Wageningen, Wageningen (Países Bajos). Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
6 figuras, 8 tablas, bib. Disponible en Español bajo CATIE ST IT-141